Extracellular Conformational Changes in the Capsid of Human Papillomaviruses Contribute to Asynchronous Uptake into Host Cells - Becker, Miriam (J Virol, 2018)
Human papillomavirus 16 (HPV16) is the leading cause of cervical cancer. For initial infection, HPV16 utilizes a novel endocytic pathway for host cell entry. Unique among viruses, uptake occurs asynchronously over a protracted period of time, with half-times between 9 and 12 h. To trigger endocytic uptake, the virus particles need to undergo a series of structural modifications after initial binding to heparan sulfate proteoglycans (HSPGs). These changes involve proteolytic cleavage of the major capsid protein L1 by kallikrein-8 (KLK8), exposure of the N terminus of the minor capsid protein L2 by cyclophilins, and cleavage of this N terminus by furin. Overall, the structural changes are thought to facilitate the engagement of an elusive secondary receptor for internalization. Here, we addressed whether structural changes are the rate-limiting steps during infectious internalization of HPV16 by using structurally primed HPV16 particles. Our findings indicate that the structural modifications mediated by cyclophilins and furin, which lead to exposure and cleavage, respectively, of the L2 N terminus contribute to the slow and asynchronous internalization kinetics, whereas conformational changes elicited by HSPG binding and KLK8 cleavage did not. However, these structural modifications accounted for only 30 to 50% of the delay in internalization. Therefore, we propose that limited internalization receptor availability for engagement of HPV16 causes slow and asynchronous internalization in addition to rate-limiting structural changes in the viral capsid. IMPORTANCE HPVs are the main cause of anogenital cancers. Their unique biology is linked to the differentiation program of skin or mucosa. Here, we analyzed another unique aspect of HPV infections using the prototype HPV16. After initial cell binding, HPVs display an unusually protracted residence time on the plasma membrane prior to asynchronous uptake. As viruses typically do not expose themselves to host immune sensing, we analyzed the underlying reasons for this unusual behavior. This study provides evidence that both extracellular structural modifications and possibly a limited availability of the internalization receptor contribute to the slow internalization process of the virus. These findings indicate that perhaps a unique niche for initial infection that could allow for rapid infection exists. In addition, our results may help to develop novel, preventive antiviral measures.